The Nanoscience and Technology of Renewable Biomaterials 2009
DOI: 10.1002/9781444307474.ch2
|View full text |Cite
|
Sign up to set email alerts
|

Biogenesis of Cellulose Nanofibrils by a Biological Nanomachine

Abstract: Cellulose is synthesized by diverse organisms including prokaryotes, protists, animals, and plants. However, cellulose achieves its natural dominance within plants, where ß-1,4-linked glucan chains form long, semi-crystalline fibrils with nanoscale lateral dimensions. Although these fibrils have been conventionally called 'microfibrils', the term 'nanofibril' may be a more appropriate name in the age of nanoscience and nanotechnology (1). This term would reflect the fibril width (ranging between ∼1.5 and 25 nm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 70 publications
(82 reference statements)
0
4
0
Order By: Relevance
“…Further work may reveal structural differences in cell walls that are deposited by proteins from the P1‐3 clades defined by AtCesA(1,3,6 or 6‐like proteins) vs. the S1‐3 clades defined by AtCesA(4,7,8) . This is a worthwhile goal for future research because uncovering potential common features of cellulose synthesized by different types of CesA proteins will aid the understanding of how particular cell wall properties are regulated at the nanoscale (Haigler and Roberts 2009). It is possible that cell wall types would be best defined by the clades of CesA proteins involved in their biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further work may reveal structural differences in cell walls that are deposited by proteins from the P1‐3 clades defined by AtCesA(1,3,6 or 6‐like proteins) vs. the S1‐3 clades defined by AtCesA(4,7,8) . This is a worthwhile goal for future research because uncovering potential common features of cellulose synthesized by different types of CesA proteins will aid the understanding of how particular cell wall properties are regulated at the nanoscale (Haigler and Roberts 2009). It is possible that cell wall types would be best defined by the clades of CesA proteins involved in their biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Although their precise role in the biochemical pathway of cellulose synthesis is still undefined, the cellulose synthases are UDP‐glucose: 1,4‐ß‐D‐glucosyltransferase enzymes in the glycosyltransferase family 2 (reviewed in Somerville 2006). In arabidopsis, members of a triplet of CesA isoforms (AtCesA1, 3, 6, or a 6‐like protein) have non‐redundant roles in primary wall cellulose synthesis (Persson et al 2007; Desprez et al 2007), whereas members of another triplet (AtCesA4, 7, 8) have non‐redundant roles in secondary wall cellulose synthesis in xylem cells (Taylor et al 2003) For convenience, the six clades that arabidopsis CesAs form with their orthologs from other seed plants have been designated P1, P2, and P3 (defined by AtCesA1, 3, and 6, respectively) and S1, S2, and S3 (defined by AtCesA 4, 7, and 8 , respectively) (Haigler and Roberts 2009). The remainder of the ten arabidopsis CesA genes appear to be relatively recently derived within P1 ( AtCesA10 ) and P3 ( AtCesA2, 5, and 9 ) in the crucifer lineage.…”
Section: Introductionmentioning
confidence: 99%
“…Cellulose is usually biosynthesized by diverse organisms and deposited in a continuous elementary microfibrils, which can be about 5-10 nm in diameter and its length varies from 100 nm to several micrometers depending on the source of cellulose [1,2]. The elementary microfibrils were made up of amorphous and crystalline parts.…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been shown that the formation of cellulose by BcsA-B requires the presence of UDP-Glc, c-di-GMP, and a divalent cation such as Mg 2+ or Mn 2+ . , However, the impact of BcsA-B surface immobilization on the nature and morphology of the synthesized cellulose has not been explored to date. Therefore, we immobilized polyhistidine-tagged BcsA-B on Ni surfaces at different surface densities and initiated cellulose biosynthesis upon addition of UDP-Glc, c-di-GMP, and Mg 2+ and imaged product formation by atomic force microscopy (AFM).…”
Section: Resultsmentioning
confidence: 99%